Hydroboration of Alkenes and Alkynes Employing Earth‐Abundant Metal Catalysts. Issue 3 (28th November 2019) - Singh, Arpita; Shafiei‐Haghighi, Sara; Smith, Cecilia R.; Unruh, Daniel K.; Findlater, Michael
Abstract: Iron complexes [BIAN]Fe(I)(η 6 ‐toluene) (M1 ) and [BIAN]FeCl2 (M2 ) (BIAN=bis(2, 6‐diisopropylaniline)acenaphthene) were found to be viable catalysts for the regioselective hydroboration of alkynes and alkenes. The hydroboration of alkynes and alkenes in the presence of HBpin and an activator at 70 °C afforded linear vinyl and alkyl boronic esters, respectively. Selectivity up to 98% was observed for alkyl boronic esters and exclusive formation of trans product was observed for vinyl boronic esters. Abstract : Iron‐ically different, but the same : Hydroboration of alkynes and alkenes is catalyzed by a [BIAN−Fe] complex in which initial substrate coordination may occur in an η 2 ‐ or η 6 ‐fashion, depending on the presence or absence of an arene moiety in the substrate. This may give rise to differing mechanisms within the same substrate class.